2003
DOI: 10.1002/smj.369
|View full text |Cite
|
Sign up to set email alerts
|

Strategy and industry effects on profitability: evidence from Greece

Abstract: The present study examines the impact of firm and industry-specific factors on profitability, using census data on Greek manufacturing. At the firm level, particular attention is given to strategy effects. Based on a modification of Porter's typology, these effects are captured through different forms of both 'pure' and 'hybrid' strategies. Industry effects are represented using industry concentration, entry barriers, and growth. Hypotheses are developed taking into account both previous research and the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
288
2
18

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(343 citation statements)
references
References 135 publications
24
288
2
18
Order By: Relevance
“…According to Porter (1980), cost improvement implies that the firm is constantly becoming more cost efficient, by improving its ability to produce at costs lower than the competition, by emphasizing efficient-scale facilities, vigorously pursuing cost reductions along the value chain driven by experience, tightly controlling cost and overhead, and minimizing cost (Spanos et al, 2004). This cost improvement strategy can also provide above-average returns because it allows the firm to lower prices to match those of competitors and still earn profits.…”
Section: Cost Improvement and Firm Profitabilitymentioning
confidence: 99%
“…According to Porter (1980), cost improvement implies that the firm is constantly becoming more cost efficient, by improving its ability to produce at costs lower than the competition, by emphasizing efficient-scale facilities, vigorously pursuing cost reductions along the value chain driven by experience, tightly controlling cost and overhead, and minimizing cost (Spanos et al, 2004). This cost improvement strategy can also provide above-average returns because it allows the firm to lower prices to match those of competitors and still earn profits.…”
Section: Cost Improvement and Firm Profitabilitymentioning
confidence: 99%
“…However, another empirical study by Pertusa-Ortega et al (2009, 520) demonstrated that low cost and differentiation strategies can be developed in a complimentary way. Spanos, Zaralis and Lioukas (2004) support the superiority of hybrid strategy over the pure forms for competitive advantage in Greek firms. Similarly, empirical study by Salavou (2010) showed that hybridists (service firms placing high emphasis on low cost and differentiation) are better performers compared with non-strategists (strategy-less firms) and confused strategists (service firms placing medium emphasis on differentiation).…”
Section: Discussion On Pure or Hybrid Strategymentioning
confidence: 61%
“…In practice it is diffi cult, however, to make a clear distinction between development concepts realised by an enterprise, and other researchers have indicated application values of hybrid, mixed, integrated or combination strategies (Hill 1988, pp. 265-98), demonstrating that these are more effective than pure strategies (Spanos et al 2004, pp. 139-65).…”
Section: Literature Reviewmentioning
confidence: 99%